2019
DOI: 10.1136/bmjopen-2019-031151
|View full text |Cite
|
Sign up to set email alerts
|

Partially randomised patient preference trials as an alternative design to randomised controlled trials: systematic review and meta-analyses

Abstract: ObjectiveRandomised controlled trials (RCT) are the gold standard to provide unbiased data. However, when patients have a treatment preference, randomisation may influence participation and outcomes (eg, external and internal validity). The aim of this study was to assess the influence of patients’ preference in RCTs by analysing partially randomised patient preference trials (RPPT); an RCT and preference cohort combined.DesignSystematic review and meta-analyses.Data sourcesMEDLINE, Embase, PsycINFO and the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 83 publications
1
75
1
Order By: Relevance
“…However, a traditional RCT has several downsides when it comes to internal and external validity in fistula patients that often have a distinct preference for their treatment 26 . Given the specific nature of the hyperbaric oxygen treatment, a patient preference model or Trial within Cohorts (TwiCs) design might be more appropriate 31,32 . It might also be interesting to investigate different approaches using hyperbaric oxygen therapy, such as treatment of patients with new fistulas (instead of therapy‐refractory ones) or pre‐ and post‐operative treatment with hyperbaric oxygen therapy around definitive surgical closure.…”
Section: Discussionmentioning
confidence: 99%
“…However, a traditional RCT has several downsides when it comes to internal and external validity in fistula patients that often have a distinct preference for their treatment 26 . Given the specific nature of the hyperbaric oxygen treatment, a patient preference model or Trial within Cohorts (TwiCs) design might be more appropriate 31,32 . It might also be interesting to investigate different approaches using hyperbaric oxygen therapy, such as treatment of patients with new fistulas (instead of therapy‐refractory ones) or pre‐ and post‐operative treatment with hyperbaric oxygen therapy around definitive surgical closure.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these factors have implications for determining treatment effects and future intervention implementation. 49 There is increasing recognition that novel trial designs may be indicated when evaluating complex interventions and a Partially Randomised Patient Preference Trial, where participants without preference are randomised, while those with a preference receive their choice would provide information on both the efficacy of the intervention and the influence of preference. 49 50 …”
Section: Discussionmentioning
confidence: 99%
“…The reason for including this preference arm was an attempt to avoid inclusion bias in the current setting in which many physicians feel glucocorticoids may have a beneficial effect in COVID-19 despite the absence of evidence from controlled clinical trials. The incorporation of patient and/or physician preferences is based on the well-described preference trial designs, which allows incorporation of patient preferences [ 24 , 25 ].…”
Section: Patients Materials and Methodsmentioning
confidence: 99%